Three new species from Southeast Asia of Euidothrips Ananthakrishnan (Thysanoptera, Thripidae, Panchaetothripinae) - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2010)
Three new species are described in the previously monotypic genus Euidothrips of the subfamily Panchaetothripinae: from Bali, E. antennatus n. sp. and E. longicornis n. sp., and from Borneo, E. borneoensis n. sp. An illustrated key is provided to the four species of the genus.